Measuring the Average Peak Timing of Kinematic Variables in Youth and Adolescent Baseball Pitchers - Mark Boland; Daniel Zambanini; Ivan Mulligan; Sean Donegan (North American Sports Medicine Institute, 2023)
# Background Previous studies have examined the timing of peak kinematic variables during the pitching cycle in high school, collegiate, and professional pitchers. These same variables have been studied less in younger populations. # Purpose To determine whether youth and adolescent baseball pitchers will experience peaks in certain kinematic variables at different times throughout the pitching cycle compared to professional/collegiate pitchers. # Study Design Cross-sectional, descriptive study # Methods Twenty-four participants were recruited for testing consisting of five recorded pitches using 3-Dimensional VICON® motion analysis system. The maximum values and timing of the peak kinematic variables were averaged across all trials using VICON Polygon® data analysis software. These values were recorded as percentages of the pitching cycle, defined from foot contact (0%) to ball release (100%). The following variables were examined: shoulder external rotation range of motion, shoulder internal rotation velocity, trunk rotation range of motion, trunk rotation velocity, pelvic rotation velocity, and stride length. Descriptive outcomes were calculated and results were compared to previous studies examining the same variables in collegiate and professional pitchers. # Results Twenty-four male participants (mean age 12.75 years, SD ± 2.02) were included in the study. Mean and standard deviations were identified for peak kinematic variables of shoulder external rotation ROM (158.71°, ±9.32), shoulder internal rotation velocity (92.26 rad/sec, ±19.29), trunk rotation velocity (15.94 rad/sec, ±1.68), trunk rotation ROM (23.57°, ±8.14), and average stride length (81.97% height ±4.57). Additionally, mean and standard deviations of peak kinematic variables were expressed as percentages to reflect when they occurred in the pitching cycle and included trunk rotation ROM (8.45%, ±12.72), pelvic rotation velocity (33.26%, ±16.42), trunk rotation velocity (41.59%, ±9.27), shoulder external rotation ROM (71.34%, ±6.61), and shoulder internal rotation velocity (86.93%, ±6.45). # Conclusion The sequential order of each variable was similar in youth and adolescents in comparison to collegiate and professional pitchers. However, the timing of each variable within the pitching cycle occurred approximately 10% earlier in the younger pitchers. The findings suggest differences in pitching mechanics exist between younger and more experienced populations. # Level of Evidence Level 3